Peran Creative Marketing dalam Membangun Brand Awareness Melalui Konten Digital di PT Inovasi Teknologi Solusindo (Trustmedis) - Riyanti Putri, Rindiantika Adinda; Purwanto, Sugeng (Innovative: Journal Of Social Science Research, 2025)
The advancement of digital technology has led companies to transform their marketing strategies, including in the healthcare sector. This study aims to examine the role of the Creative Marketing Team at PT Inovasi Teknologi Solusindo (Trustmedis) in building brand awareness through digital content. The method used involved direct observation and participation in content creation during an internship. The findings show that the use of content pillars (awareness, consideration, conversion), planning through a content calendar, and the implementation of appropriate Calls to Action (CTAs) can enhance brand exposure and generate qualified leads. In conclusion, the digital content strategy implemented by Trustmedis’s Creative Marketing Team contributes positively to achieving the company's marketing goals.